Effectiveness of The Use of Basic Atletic Motion Learning Model Based on Traditional Games to Improve Skills at Run 40 Meters - Elisyah, Veni; Tangkudung, James; Puspitorini, Wahyuningtyas; Kristina, Putri Cicilia (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
Athletics is a competitive physical activity that is like walking, running, throwing, and jumping, so it is not uncommon for this sport to be said to be the parent of another sport because it has a variety of movements in it. This type of research is quasi-experimental research with a quantitative descriptive approach using the one group control pretest-posttest design research design. The results showed that the basic motion learning model of the 40-meter athletic run based on traditional games was effective to be applied to elementary school students as evidenced by the results of the N-gain score showed that the average N-gain score for the experimental class was 79, 21% included in the Ã¢â‚¬Å“effectiveÃ¢â‚¬Â category. It is suggested that teachers and students should be able to use the basic 40-meter athletic basic motion learning model based on traditional games as alternative learning for students and as a reference for physical education teachers in elementary schools.